2018
DOI: 10.5888/pcd15.170147
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Online Information-Seeking and Adherence to Guidelines for Breast and Prostate Cancer Screening

Abstract: IntroductionFrom 2012 through 2014, the US Preventive Services Task Force (USPSTF) recommended biennial mammography for women aged 50 to 75 and recommended against the prostate specific antigen (PSA) test for men of any age, emphasizing informed decision making for patients. Because of time constraints and other patient health priorities, health care providers often do not discuss benefits and risks associated with cancer screening. We analyzed the association between seeking information online about breast an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…While our analysis has identified the range of strategies used to nudge towards participation, a limitation of a multimodal critical discourse analysis is that it only demonstrates the meaning potential inherent in a text, and cannot make claims about the writer’s intentions or how individual readers will receive a text (Kim et al, 2018; Machin & Mayr, 2012). Moreover, our analysis is based on web pages as they were at one specific moment in time, and content may have been changed since.…”
Section: Discussionmentioning
confidence: 99%
“…While our analysis has identified the range of strategies used to nudge towards participation, a limitation of a multimodal critical discourse analysis is that it only demonstrates the meaning potential inherent in a text, and cannot make claims about the writer’s intentions or how individual readers will receive a text (Kim et al, 2018; Machin & Mayr, 2012). Moreover, our analysis is based on web pages as they were at one specific moment in time, and content may have been changed since.…”
Section: Discussionmentioning
confidence: 99%
“…As such, by applying a multifaceted design this study first confirmed the existence of this difference and built upon it by including SES level in an interaction analysis of marginal structural models, and then examined in-depth factors contributing to this difference by using Blinder–Oaxaca decomposition. As far as we are aware, this is the first study that has applied Oaxaca decomposition to oral cancer screening, though its use has been found in studies of disparities in other cancer screenings such as lung, breast, and prostate [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many hospitals still decide whether to conduct prostate biopsies based on the PSA level. There is little evidence that the USPSTF guidelines significantly affect people who seek prostate cancer screening [ 20 ]. Therefore, more precise biopsies and delicate patient selection are required.…”
Section: Discussionmentioning
confidence: 99%